Evaluation of Surface Roughness and Compressive Strength of Modified Glass Ionomer Cement with Coumarin Derivatives / Nor Ain Fatihah Azlisham...[et al.] - Azlisham, Nor Ain Fatihah; Mahmood, Zuliani; Mohamad, Dasmawati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The objective of the present study was to evaluate the effect of incorporation of synthesized coumarin derivatives, hydrazinyl thiosemicarbazide (HZTC), an antibacterial agent on the surface roughness and compressive strength of glass ionomer cements (GICs). Two commercial GICs, Fuji II LC and Fuji VII were used in this study and act as control groups. HZTC was incorporated into GIC during its manipulation at the weight percentage of 1% and 2%. The surface roughness and compressive strength of the samples were prepared and analysed using Profilometer and universal testing machine Shimadzu AGX-Plus respectively. The data were analysed statistically to determine the significant differences among groups using Kruskal Wallis and Man Whitney test for the surface roughness, and one-way ANOVA with post-hoc Bonferonni test for the compressive strength. Statistically, the surface roughness value of Fuji II LC was significantly increased (p<0.05) at both weight percentages while the decrease value of Fuji VII was insignificant at 1% (w/w) compared to the control GICs. The compressive strength of both Fuji II LC and Fuji VII showed significantly decreased in strength values (p<0.05) at both weight percentages compared to the control GICs. Based on the results of this study, it can be concluded that the incorporation of HZTC gave measurable effects on the surface roughness and compressive strength values.